Leaching of plant nutrients from cultivated soils: I Leaching of cations - Hartikainen, Helinä (Agricultural and Food Science, 1978)
Leaching of native and added basic cations was studied in a lysimeter experiment. The trial was carried out with three surface soil samples: sand, fine sand and sandy clay. The effect of the acidic precipitation on the leaching losses was studied by using 0.025 M sulfuric acid as irrigation solution. The cation concentration in the leachate seemed to be determined by the CEO of the soil sample. The relative and absolute leaching losses were lowest in the sandy clay and highest in the sand soil. Five percolations extracted most abundantly calcium and least abundantly sodium, the losses of magnesium and potassium were of about the same magnitude. In regard to cation reserves of the soils the relative amounts leached usually followed the sequence: Na >Mg≈ Ca>K. Fertilization seemed to promote the leaching of cations, especially that of soil calcium. Water extracted 10 to 37 % of added magnesium, but only 2 to 6 % of added potassium due to the effective retention. The acid in the irrigation water increased the losses of all cations studied, most drastically the losses of divalent ones.